(3JGQjN GdOhdJjf GdehMOjI hGdMaUqjIs - (3eMeO Hf EHQGgje Hf dDdD, GdeYQha HGdRQcTj,J (B932 (3g` s
(3ChdgG (B:s
(3hHYO , aEf GdEeGe GdegOj QMeg Gddg gh eMeO Hf YHOGddg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B302 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B214s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B456 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B677 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B78 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs